1992
DOI: 10.1002/path.1711670106
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in apoptosis relative to mitosis in histologically normal epithelium accompanies fibrocystic change and carcinoma of the premenopausal human breast

Abstract: The aims of this study in 227 premenopausal women were (a) to determine the mitotic index (MI), the thymidine labelling index (LI), and the apoptotic index (AI) within the epithelial cells of histologically 'normal' human breast biopsy material removed away from the site of either a fibroadenoma or a carcinoma; and (b) to relate differences in the kinetic indices of the 'normal' epithelium to the pathology in the same breast diagnosed as fibroadenoma alone (125 patients), fibroadenoma with accompanying mild fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 12 publications
7
48
0
3
Order By: Relevance
“…Furthermore, we have noted Al to be closely related to the nuclear grade of the DCIS lesions (Figure 2). Whereas Bodis et al (1996) failed to find any evidence of apoptosis in grade 1 DCIS lesions, we have found the median Al in nuclear grade 1 DCIS lesions to be 0.35%, a value similar to that described in normal breast epithelium taken from women undergoing a breast biopsy for fibroadenoma [0.33% and 0.35% by Allan et al (1992) and Potten et al (1988) respectively]. It is unlikely that apoptosis is present.in normal epithelium yet totally absent in malignancy (DCIS), and our finding of genetically programmed cell death in grade 1 DCIS probably represents the 'background' apoptosis seen in normal breast tissue.…”
Section: Apoptotic and Proliferative Indicessupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, we have noted Al to be closely related to the nuclear grade of the DCIS lesions (Figure 2). Whereas Bodis et al (1996) failed to find any evidence of apoptosis in grade 1 DCIS lesions, we have found the median Al in nuclear grade 1 DCIS lesions to be 0.35%, a value similar to that described in normal breast epithelium taken from women undergoing a breast biopsy for fibroadenoma [0.33% and 0.35% by Allan et al (1992) and Potten et al (1988) respectively]. It is unlikely that apoptosis is present.in normal epithelium yet totally absent in malignancy (DCIS), and our finding of genetically programmed cell death in grade 1 DCIS probably represents the 'background' apoptosis seen in normal breast tissue.…”
Section: Apoptotic and Proliferative Indicessupporting
confidence: 75%
“…Cells undergoing apoptotic death display characteristic morphological features and are removed by phagocytosis in the absence of any inflammatory response, thereby permitting cell death without damage to adjacent cells (Schwartzman and Cidlowski, 1993;Kerr et al, 1994). Apoptosis is believed to act as the counterbalance to proliferation (mitosis) and is a critical factor in tissue homeostasis (Potten, 1992). Dysregulation of the apoptotic process may therefore play a crucial role in oncogenesis.…”
mentioning
confidence: 99%
“…In a previous study, we have shown breast cancer cells exhibit reduced apoptosis compared to normal breast epithelium (Shao et al, 1996). Investigators in another study reported reduced breast epithelial cell apoptosis in association with fibrocystic disease and an increased risk of carcinoma (Allan et al, 1992). Other investigators have shown that the inhibition of apoptosis is linked to tumour promotion (Tomei et al, 1988).…”
Section: Discussionmentioning
confidence: 75%
“…64 These findings of reduced apoptosis are relevant since decreased mammary epithelial apoptosis is associated with an increased risk of fibrocystic changes and the development of carcinoma in premenopausal women. 65 We are currently breeding our MMTV-IGF-II transgenic mice with mice that overexpress the neu oncogene to examine whether IGF-II-mediated inhibition of epithelial apoptosis augments neu-induced mammary tumorigenesis.…”
Section: The Antiapoptotic Property Of Igf-ii May Underlie Its Tumorimentioning
confidence: 99%